2004
DOI: 10.1093/geront/44.6.788
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse of Older Adults: APS Cases and Outcomes

Abstract: Orientation affects the invasiveness of the sexual abuse experienced by older adults. Our data reveal a small but persistent number of cases identifying individuals who are especially vulnerable to this form of abuse. These findings establish a baseline for future research and set the stage for further examination in both domestic and institutional settings as well as possible interventions and staff training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 7 publications
2
69
0
5
Order By: Relevance
“…Specifically, self-reported victimization was linked with a reduction in life satisfaction and a greater risk for depression, anxiety, loneliness, low self-esteem and overall negative mood (Trompetter et al, 2011). Disturbingly, there is evidence that victims of RRA were shown to be four times more likely to experience neglect from nursing home staff (Zhang et al, 2011), and that victims of sexual RRA did not receive any post-care for addressing the assault (Teaster & Roberto, 2003;Teaster & Roberto, 2004;Teaster et al, 2007). Clearly, to focus energies solely on the description of a potentially life-threatening event is not sufficient, and is likely to be of little comfort to residents' and their A c c e p t e d M a n u s c r i p t 25 families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, self-reported victimization was linked with a reduction in life satisfaction and a greater risk for depression, anxiety, loneliness, low self-esteem and overall negative mood (Trompetter et al, 2011). Disturbingly, there is evidence that victims of RRA were shown to be four times more likely to experience neglect from nursing home staff (Zhang et al, 2011), and that victims of sexual RRA did not receive any post-care for addressing the assault (Teaster & Roberto, 2003;Teaster & Roberto, 2004;Teaster et al, 2007). Clearly, to focus energies solely on the description of a potentially life-threatening event is not sufficient, and is likely to be of little comfort to residents' and their A c c e p t e d M a n u s c r i p t 25 families.…”
Section: Discussionmentioning
confidence: 99%
“…Victims of RRA are often female residents(Burgess & Phillips, 2006;Ramsey-Klawsnik et al, 2008;Teaster & Roberto, 2004) who are cognitively impaired(Burgess et al, 2000;Burgess & Phillips, 2006;Malone et al, 1993;Ramsey-Klawsnik et al, 2008;Rosen et al, 2008a;Rosen, Lachs, & Pillemer, 2010;Shinoda-Tagawa et al, 2004;Sifford-Snellgrove, Beck, Green, & McSweeney, 2012;Teaster & Roberto, 2004) and who exhibit wandering behaviors(Rosen et al, 2008a;Shinoda-Tagawa et al, 2004;Sifford-Snellgrove et al, 2012). Within the context of understanding RRA occurrences,Soreff (2012) points out that that victims typically fall into three categories: unintentional victim (resident may unintentionally provoke another resident),…”
mentioning
confidence: 99%
“…Two (one employee and one resident) admitted sexually abusing residents and one admitted physical abuse. Teaster and Roberto (2004) found that the majority of perpetrators of sexual abuse of 82 adults aged 60 and older were other nursing home residents. A subsequent study of 125 substantiated Virginia cases of sexual abuse comparing older and younger female victims (Roberto & Teaster, 2005) found that perpetrators against older women were most commonly fellow facility residents, while those who assaulted women under age 60 years were primarily family members.…”
Section: Characteristics Of Alleged Perpetratorsmentioning
confidence: 99%
“…Despite the fact that various forms of elder mistreatment are underreported (Lifespan of Greater Rochester; Pillemer, & Finkelhor, 1988), no type is thought to be so underreported as that of sexual abuse (Brozowski & Hall, 2010; Ramsey-Klawsnik, Teaster, Mendiondo, Marcum, & Abner, 2008; Rosen, Lachs, & Pillemer, 2010; Teaster & Roberto, 2004). Sexual abuse is defined as “non-consenting sexual contact of any kind” (National Center on Elder Abuse [NCEA], 1995, p.1), and includes unwanted touching; sexual assault or battery, such as rape, sodomy, and coerced nudity; sexually explicit photographing; and sexual contact with any person incapable of giving consent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most research conducted on the sexual victimization of older adults has reported primarily female victims (Burgess, Ramsey-Klawsnik & Gregorian, 2008; Ramsey-Klawsnik, 1996; 2003; Teaster & Roberto, 2004), with a paucity of studies examining the sexual victimization of older men (Teaster et al, 2007; Roberto, Teaster, & Nikzad, 2007). …”
Section: Literature Reviewmentioning
confidence: 99%